Leader of Character Framework for Bachelor Degree in Maritime Technology Graduates - M.R, Zulkifly; J.W, Tang; I, Sarah; A.R., Ainul; R., Afiqah; Afizi M.S., Mohd (International Journal of Engineering and Technology, 2018)
The current employability of Bachelor Degree in Maritime Technology graduates needs to be improved to meet the requirements of stakeholders such as Royal Malaysian Navy, maritime agencies and industries. Hence, the curriculum of this degree needs to be reviewed to produce the right graduate to serve the maritime agencies and industries. The research was done through brainstorming, discussion, meeting and decision by a Committee Member established by the faculty. The finding of the committee concluded that all UPNM students will be assessed on six attributes as Leaders of Character which include: a graduate officer, commissioned officer, sports person, imam, master in self-defence, and lastly an officer and a gentleman or lady. The graduate officer assessment is based on academic performance reflected in his/her CGPA to be above 2.7. The naval cadet officer assessment is based on the successful completion of training to be commissioned into Royal Malaysian Navy. To be a sports person, a student must register in at least one sport in the co-curriculum courses. The spiritual leader assessment for a Muslim to an imam and to read sermon during Friday prayers whereas a Non-Muslim will learn to pray and worship in his/her religion. Self-defence will be assessed through self-defence courses such as taekwondo or other parts of self-defence. An officer and a gentleman or lady is assessed by observing on the attitudes, ethics, morals, courtesy, positive values, determination, behaviour and lastly discipline. The assessments are reported through radar plots, which include six attributes in the LoC. The Bachelor Degree in Maritime Technology graduate who acquires all the six attributes will be awarded with a Diploma in LoC as an added value in their degree for their future employment.Â